PESAN KAMPANYE #PADATEMPATNYA TERHADAP SIKAP MENDUKUNG PERILAKU HIDUP BERSIH DAN SEHAT (PHBS) MASYARAKAT: Survei Pada Pengunjung XXI di City Plaza Jatinegara - AULIA NURUL KHOTIMAH (2020)
The increasing number of cinema screens affects the number of cinema viewers. Therefore, there is the potential for visitors to leave trash in the cinema that needs to be overcome in order to support clean and healthy living behaviors (PHBS). The purpose of this study was to prove the influence of #PadaTempatnya campaign messages on the supportive attitude of PHBS in the community. The approach used in this study is a quantitative survey that tests the Information Integration Theory on XXI visitors at City Plaza Jatinegara as many as 100 people. The sample technique used was accidental sampling while data processing used a questionnaire. Campaign messages are measured based on two (2) dimensions namely Message Content and Message Structure while attitude is measured based on three (3) dimensions namely cognitive, affective, and conative. Regression test results show that the direction of the influence of the #PadaTempatnya campaign messages with the supportive attitude of PHBS in the community is positive. The results of the coefficient of determination indicate that there is an influence of 66.4% between campaign messages to the supportive attitude of PHBS in the community. These results are strengthened by the results of a hypothesis test which states that Ho was rejected and Ha was accepted, meaning that there is an influence between the campaign messages on the supportive attitude of PHBS in the community. The conclusion of the study is the #PadaTempatnya campaign messages influence the supportive attitude of PHBS in the community, especially on XXI cinema visitors at City Plaza Jatinegara.